2021
DOI: 10.1002/pts.2557
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low‐acceleration, long‐duration horizontal events using a spring suspension straight delivery box truck

Abstract: A field measurement study, using a combination of controlled and uncontrolled phases, examined low‐acceleration, long‐duration events occurring during over‐the‐road truck transport. A field data recorder equipped with a DC‐based triaxial accelerometer was employed for this study to capture the steady‐state nature of these event types. The field data recorder was rigidly mounted to the trailer chassis to record lateral and longitudinal events of interest. The controlled phase recorded normal and aggressive brak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
14
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 20 publications
7
14
4
Order By: Relevance
“…Figure 4 displays the frequency of events for all recorded longitudinal events, indicating the majority of all events fall below 0.32 g. These values are significantly less than currently available literature, which states deceleration values as high as 0.8 g in the stopping direction 21 . This study's results align with previous studies that reported average accelerations ranged from 0.27 to 0.33 g for normal braking instances during truck transport 28,29,32 . The CDFs show the percentage of the events that are below a certain measured peak deceleration value.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Figure 4 displays the frequency of events for all recorded longitudinal events, indicating the majority of all events fall below 0.32 g. These values are significantly less than currently available literature, which states deceleration values as high as 0.8 g in the stopping direction 21 . This study's results align with previous studies that reported average accelerations ranged from 0.27 to 0.33 g for normal braking instances during truck transport 28,29,32 . The CDFs show the percentage of the events that are below a certain measured peak deceleration value.…”
Section: Resultssupporting
confidence: 88%
“…The braking application behaviour in the present study is more typical for normal transport conditions. Additionally, the d tr for this study's braking events are significantly longer than previously reported studies, indicating smaller vehicles with lighter payload can achieve shorter rise times 28,31 …”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations